Can Science Reveal the Origin of the Universe? - Cui, Weicheng (European Journal of Applied Sciences, 2024)
Recently Nature published an influential paper and introduced a novel perspective: "Quantum theory might make the cosmos more certain than classical physics ever did." [1]. After reading this paper together with the relevant background theory, we think that this conclusion is drawn from continuous misconceptions since relativity theory, quantum mechanics and Big-Bang theory. These misconceptions include: (1) no distinction between Universe and world, thus blurred the boundary between speculative knowledge and scientific knowledge; (2) physical reality and mathematical language; (3) deterministic classical mechanics and probabilistic quantum mechanics; (4) completeness and logical consistency. In this short paper, six issues we found from reading this paper are briefly discussed and our main conclusions are that science cannot reveal the origin of whole Universe but a concrete system within the world we can observe. Scientific theory should not be required to be complete in order to keep its logical consistency. We should not interpret a scientific theory to be either deterministic or probabilistic and this depends on the information available to us for the model parameters. The clarification of these issues may be helpful to promote the development of cosmology theory in the track of scientific theory.